VD_FINDINFO Arrêt / 2015 / 907 vom 29. Oktober 2015 - VD Tribunal cantonal (2015)
PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE, FRAIS JUDICIAIRES | 50 LPA-VD, 94 al. 1 let. a LPA-VD, 94 al. 1 let. c LPA-VD